Management of atypical sexual behaviors of adolescents with autism - Carlos, Christine Laura Limpin (2006)
There is a need to identify and evaluate atypical sexual expressions of adolescents with autism, as well as the management techniques used to address them. The study is a quantitative-qualitative descriptive research on the management approaches for atypical sexual behaviors (ASBs) in adolescents with autism (AWAs). Twenty SPED teachers were involved in the study. Thorough interviews and researcher-designed instruments were used. Results showed that inappropriate behaviors are not seen in all adolescents with autism but are undeniably present in some. Respondents reported that the three most common ASBs are inappropriate masturbation, inappropriate sexual behaviors towards others and exposure of private parts in public. Availability of resources regarding this topic were noted to be present, however scant.
"October 2006."
Thesis (M.A. Education : Special Education)--University of the Philippines, Diliman.
Keywords: Autistic youth -- Sexual behavior -- Philippines; Sexual harrassment in education -- Philippines -- Prevention; Special education teachers -- Philippines